Learning strategies in Colombian undergraduate and graduate students (2020)
This research article expounds the importance of the teacher learning quality and analyzes the learning strategies in undergraduate and graduate students of Education programs. A non-probability sampling including 534 students was used. They were applied the scales Support and Control Strategies and Strategies Related to Information Processing from the CEVEAPEU questionnaire, an instrument to assess the learning strategies of university students. The results show significant differences in the use of strategies between the students who start the undergraduate programs and those finishing the graduate programs. Within the graduate students there are no significant differences in the use of learning strategies. © 2020 Pontificia Universidad Javeriana. All rights reserved.